Students' participation in university governance in South Africa - Mthethwa, Vuyo (AOSIS, 2022)
The purpose of this book is to examine the academic experiences of students who participated in university governance at South African universities. Scrutiny is placed on the alignment of student representative council constitutions and university statutes with the actual experiences students had in discharging their roles in governance and in the way this impacted their academic progress. Through a multi-site case study design, semi-structured interviews were conducted with members of the student representative council who participated in university governance and supported by document analysis and observations to generate the data. The study adopted Tinto's Integration Theory and Astin's Theory of Involvement as the two frameworks are based on the relationship between students' extra-curricular activity and their academic experiences. The study invokes a greater awareness of students as major stakeholder in governance and informs policies and practices that may better serve students' academic experiences. The study will contribute to the understanding of cooperative governance principles while drawing from the perspective of the students on their understanding, limitations and challenges in discharging their roles in university governance.